2021
DOI: 10.1016/j.jinf.2020.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Prior SARS-CoV-2 infection is associated with protection against symptomatic reinfection

Abstract: Prior SARS-CoV-2 infection is associated with protection against symptomatic reinfectionTo the editor, It has been recently suggested that prior exposure to seasonal coronaviruses might confer cross-protection against SARS-CoV-2. 1 Whether SARS-CoV-2 infection itself confers immunity to reinfection has not been established. Immunity is probable, at least in the short term, because reinfections are infrequently reported, despite over 55 million primary infections occurring worldwide since December 2019. 2 Prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
116
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(128 citation statements)
references
References 10 publications
11
116
0
1
Order By: Relevance
“…This relationship has already been highlighted in the acute phase studies 8 and our data add information on midterm follow-up (approximately 7 months) according to COVID-19 severity. Our observation of no symptomatic reinfection is in line with the low rate of reinfection reported in the literature suggesting a likely immunity provided by the natural infection which persist in the midterm 1 . Furthermore, some of the recently developed vaccines base their theoretical efficacy on the production of on the S1 + S2 protein antibodies 9 .…”
Section: Letter To the Editorsupporting
confidence: 90%
See 1 more Smart Citation
“…This relationship has already been highlighted in the acute phase studies 8 and our data add information on midterm follow-up (approximately 7 months) according to COVID-19 severity. Our observation of no symptomatic reinfection is in line with the low rate of reinfection reported in the literature suggesting a likely immunity provided by the natural infection which persist in the midterm 1 . Furthermore, some of the recently developed vaccines base their theoretical efficacy on the production of on the S1 + S2 protein antibodies 9 .…”
Section: Letter To the Editorsupporting
confidence: 90%
“…Is COVID-19 severity associated with anti-spike antibody duration? Data from the ARCOVID prospective observational study Dear Editor, we read with interest the article by AT Hanrath and colleagues in which the Authors showed the association between prior SARS-CoV-2 infection and protection against symptomatic reinfection 1 . The study confirms the need for a better understanding of the immunological response to SARS-CoV-2 infection.…”
Section: Letter To the Editormentioning
confidence: 99%
“…1,2 A key question concerning measures against COVID-19 is the strength and durability of immunity against this disease in individuals previously infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). [3][4][5][6][7][8][9][10] Vaccination strategies, considerations regarding herd immunity, and overall simulations for the pandemic depend on the efficacy and the time course of immunity against COVID-19. 5 Data on immune responses to COVID-19 are limited by knowledge gaps regarding their dynamics over time and their clinical significance with reference to protection against re-infections.…”
Section: Introductionmentioning
confidence: 99%
“…5 Data on immune responses to COVID-19 are limited by knowledge gaps regarding their dynamics over time and their clinical significance with reference to protection against re-infections. [3][4][5][6][7][8][9][10] There is evidence for re-infections from numerous case reports, but it is occasionally challenging to differentiate true re-infections from prolonged viral shedding that may last for up to about 4 months. 5,11,12 Notably, a study of 12,541 health care workers in the UK recently found major protection against re-infection for those who had anti-SARS-CoV-2 antibodies determined by anti-spike and anti-nucleocapsid assays versus those who did not.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation